2004
DOI: 10.1021/cm049605a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Gold Island Films on Silanized Glass. Morphology and Optical Properties

Abstract: Evaporated gold island films have been the subject of studies dealing with a variety of spectroscopic and sensing applications. Development of these and other applications requires film stability as well as tunability of the morphology and optical properties of the island films. In the present work, ultrathin, island-type gold films were prepared by evaporation of 1.0-15.0 nm (nominal thickness) gold at a rate of 0.005-0.012 nm s -1 onto glass substrates modified with 3-mercaptopropyl trimethoxysilane (MPTS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
218
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 200 publications
(248 citation statements)
references
References 49 publications
(84 reference statements)
26
218
1
3
Order By: Relevance
“…Different gold nanoisland films were generated from Au NPs-PAH multilayer films with two, five or eight layers of gold nanoparticles after annealing at ~ 500 o C. The optical properties of the films were examined using transmission UV-vis spectroscopy (Figure 3), showing strong SP bands around 533, 541, and 542 nm for nanoisland films generated from Au NPs-PAH 2-, 5-, and 8-nanoparticle layer films, respectively. Similar SP bands have been observed from Rubinstein's vacuum evaporated films after annealing at 200 -250 o C. 19,21 Their study showed that the increase in the optical intensity was observed upon increasing the nominal thickness of the evaporated island films. UV-vis spectra of our nanoisland films generated from Au NPs-PAH multilayer films with 2-, 5-, or 8-layers of gold nanoparticles also showed a strong dependence of the localized gold SP band intensity on the composition of gold island films.…”
Section: Formation and Characterization Of Gold Nanoisland Filmssupporting
confidence: 71%
See 4 more Smart Citations
“…Different gold nanoisland films were generated from Au NPs-PAH multilayer films with two, five or eight layers of gold nanoparticles after annealing at ~ 500 o C. The optical properties of the films were examined using transmission UV-vis spectroscopy (Figure 3), showing strong SP bands around 533, 541, and 542 nm for nanoisland films generated from Au NPs-PAH 2-, 5-, and 8-nanoparticle layer films, respectively. Similar SP bands have been observed from Rubinstein's vacuum evaporated films after annealing at 200 -250 o C. 19,21 Their study showed that the increase in the optical intensity was observed upon increasing the nominal thickness of the evaporated island films. UV-vis spectra of our nanoisland films generated from Au NPs-PAH multilayer films with 2-, 5-, or 8-layers of gold nanoparticles also showed a strong dependence of the localized gold SP band intensity on the composition of gold island films.…”
Section: Formation and Characterization Of Gold Nanoisland Filmssupporting
confidence: 71%
“…The morphologies of these nanoisland film arrays were quite comparable to those of nanoisland films prepared by vacuum evaporation method. [15][16][17][18][19][20][21][22] As shown in Figure 5, the nanoisland films generated from 8-nanoparticle layer films had more grains and the peak of the distribution moved to a lower value. Density of grains for nanoisland films from 5-and 8-nanoparticle layer films was estimated to be ~ 500 grains/µm 2 and ~ 950 grains/µm 2 , respectively.…”
Section: Formation and Characterization Of Gold Nanoisland Filmsmentioning
confidence: 93%
See 3 more Smart Citations